Spectrum of phenotype and genotype of congenital isolated hypogonadotropic hypogonadism in Asian Indians. (12th February 2016) - Nair, Sandhya; Jadhav, Swati; Lila, Anurag; Jagtap, Varsha; Bukan, Amol; Pandit, Reshma; Ekbote, Alka; Dharmalingam, Mala; Kumar, Prasanna; Kalra, Pramila; Gandhi, Pramod; Walia, Rama; et al.
Summary: Background: Congenital isolated hypogonadotropic hypogonadism (IHH) is caused due to defect in GnRH neuronal development, migration and action. Although genetic aetiology of IHH is increasingly being studied, Asian Indian data on phenotypic spectrum and genetic basis are scarce. Objective: To investigate the phenotypic and genotypic spectrum of IHH in Asian Indian subjects. Design, Setting and Subjects: A cohort of 135 IHH probands were characterized phenotypically for reproductive and nonreproductive features and screened for rare sequence variations (RSVs) in five genes KAL1, FGFR1, FGF8, GNRHR and KISS1R . Result: Of 135 probands [56 normosmic IHH (nIHH) and 79 Kallmann syndrome (KS)], 20 were familial cases. KS group had more male dominance (M:F ratio of 8:1) as compared to nIHH group (M:F ratio of 1·5:1). Complete absence of puberty was more prevalent in KS probands (81% in KS vs 46% in nIHH). The prevalence of MRI abnormalities was more in anosmic group (92·8%) as compared to hyposmic (37·5%) and normosmic groups (15·4%). No particular nonreproductive phenotypic predominance was seen in any group. Genotyping revealed rare sequence variation (RSV) detection rate of 15·5% in five genes studied: ( KAL1 – 4·4%, FGFR1 – 4·4%, GNRHR – 6·7%, oligogenicity – 1·5%). Prevalence of RSV was more common in familial cases (35%) as compared to sporadic (12·2%). GNRHR RSV p.C279Y (not reported in patients of ethnicities other than south Asians) was recurring in four unrelated patients. Conclusion: In our cohort, 60% were KS with majority of males and a severe reproductive phenotype as against nIHH. Contribution of the genetic burden for the five genes studied was 15·5%. RSV p.C279Y in GNRHR may have a founder effect originating from south Asia. This study provides a model for molecular and phenotypic representation of Asian Indian subjects with IHH.